ANALISIS PEMBERIAN KOMPENSASI DALAM MENINGKATKAN KINERJA KARYAWAN DI PERUSAHAAN DWI MULIA CUTTINDO TANGERANG - Yola Irfatunna Difa (Management Insight: Jurnal Ilmiah Manajemen, 2022)
Abstract This study aims to analyze the forms of compensation, namely financial and non-financial compensation, also analyze the compensation system and how compensation can improve employee performance at Dwi Mulia Cuttindo Tangerang Company. This study uses qualitative research method with the type of case study research, where the data collection technique is triangulation. The results showed that the form of compensation given by Dwi Mulia Cuttindo was financial compensation in the form of basic salary, meal allowance, overtime pay, bonuses and holiday allowances, non-financial compensation in the form of suitable work, a safe and comfortable work environment and facilities in the form of housing, vehicles and food. The compensation system applied is the time system. The bonus given by Dwi Mulia Cuttindo can increase employee morale and performance. However, the distribution of bonuses to employees is not evenly distributed, so employees expect a salary increase and an award in the form of bonuses for employees who do not get a bonus.Keyword: financial compensation;non-financial compensation;employee performance